Antimicrobial Study of Clinical Mastitic Milk Samples of Cows in and Around Bikaner - Morwal, Sandhya; Singh, AP; Sharma, SK; Goklaney, Deepika (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Mastitis, an inflammatory condition of the mammary gland, is one of the most economically important  diseases of dairy herds. This disease is more prevalent in  high yielding dairy cattle. It is caused due to colonization  of pathogenic bacteria causing series of events that lead to  major alteration in the mammary tissues and composition of  milk secreted from the tissue cells (Batavani et al., 2007; Goel  et al., 2008). Clinical mastitis is recognized by abnormal milk,  varying degree of mammary gland inflammation (redness,  heat, swelling and pain) with or without illness of the cow. Mastitis in dairy animals leads to heavy economic losses due  to reduction in milk production, altered composition, and  cost of treatment of affected animals. The clinical mastitis in  different cases can be identified by external symptoms such  as udder swelling, touch, pain, redness and hardness of the  udder. The objective of the present study was to assess the  sensitivity of bacterial isolates from mastitic milk samples of  cows to some selected antibiotics.
Keywords: Antibiogram; Cow; Clinical Mastitis; Milk Samples